Cognitivism and the Problem of Scientific Psychology - Gustavo Arja Castañon (Psicologia, 2010)
This article is about the problem of scientific statute of psychology. Its proposal is to evaluate in what extension cognitivism solved historical objections to the possibility of a scientific psychology. Based on an evaluation of classical texts of the “cognitive revolution”, it concludes that this approach presented a philosophical project of psychological science that solved most of the ontological and epistemological endemic problems of the discipline, like the one of non quantitative nature of psychological object, the subject and object simultaneity condition, the supposed non-existence of own object and the impossibility of psychological phenomenon direct observation. However, cognitivism ignored or worsened the problems about the possibility of some level of human autonomy and of the psychological explanation complexity. Despite its evident advances, cognitivism still doesn’t get full accomplishment of the project of ontological, epistemological and methodological fundamentation of a psychology completed adhered to modern science.